Quality information and fake news on Covid-19 and immunization among adolescents: a qualitative analysis in school settings - Nuccetelli, Fabiana; Gabellone, Valeria; Gabrielli, Elisa; Lopalco, Pier Luigi (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Correct information is an essential tool to guide thoughts, attitudes, daily choices or more important decisions such as those regarding health. Today, a huge amount of information sources and media is available. Increasing possibilities of obtaining data also require understanding and positioning skills, particularly the ability to navigate the ocean of information and to choose what is best without becoming overwhelmed. Objective. In the present study, focus group methodology has been used as a survey instrument in a school setting in order to study the knowledge, preconceptions, and attitudes of students toward vaccination practice, to promote favourable and knowledgeable attitudes about vaccination and counteract the spread of fake news. Material and methods. In an educational institution in Apulia in March 2023, 2 focus group sessions were conducted with students as part of an educational project. The selected sample of 23 students was divided into two groups consisting of 12 and 11 participants each, respectively, chosen through the probabilistic method. The knowledge and attitude baseline was assessed through a structured questionnaire at the start of the day. Then, before the focus group sessions, the first group (A) was exposed to an informative video conducted by an expert on the topic of vaccination and fake news, while the second group (B) attended a frontal lesson on the same issues. The guiding questions that the moderators considered in both groups for the topic of vaccination investigated the importance, the usefulness of vaccines, and the trust in political authorities. Results. The responses to the initial questionnaire revealed high variability among the two groups, although they were randomly selected. Transcripts of the dialogues were categorized by ATLAS.ti into 204 total codes and 87 categories, then combined to form increasingly generic categories that were united by related themes. It was developed in a specific model of favouring and hindering factors divided into 4 thematic domains specially adapted to the school context: perception of disease risk, emotional aspects, beliefs about the vaccine, and attitudes toward fake news. Discussion. The category “Fake News” with 97 mentions turns out to be the most discussed by students within all the explored domains. Adolescents have a greater attitude to be overcome by conspiracy theories, probably because they are more exposed to online news. We could detect a generalised sense of confusion with respect to the communication of the pandemic period that emphasised, in many of them, prior perplexities. Public health policies, criticised by the participants, led them to develop a sceptical and conspiratorial attitude toward the authorities, claiming economic interests behind some management choices. “Emotions,” with 63 quotes, confirmed the strong impact of the emotional sphere, multifaceted and diverse, on adolescents’ personal experience during the pandemic. Conclusions. The results suggest that a single intervention (video or lesson) is not able to change attitudes and thinking tendencies of the adolescents examined. In addition, the leader figure present in both groups, was found to influence, in both study conditions (group A and group B), students’ opinions, especially on the issue of fake news, more than a short-term intervention.